Prevalence and frequency of self-management strategies among female cancer survivors: the neglected roles of social relations and conscious living - Sieverding, Monika; Ungar, Nadine; Fleischmann, Alexandra; Lee, Miruh; Zhang, Haitong; Mohnke, Margaux; Specht, Nicole; Weidner, Gerdi (Supportive care in cancer, 2020)
To assess prevalence and frequency of use of self-management strategies among female cancer survivors and to empirically identify categories of self-management.